Cluster-Based Strategies for Enhancing BTS Infrastructure and Cellular Signal Coverage in Indonesian Villages - Ari Wibowo, Ristiaji; Tri, Dewie; Amelia, Ratih; Fitro, Achmad (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
This study investigates the enhancement of Base Transceiver Station (BTS) infrastructure and cellular signal coverage in Indonesian villages from 2021 to 2023. Provinces were classified using clustering techniques into three distinct groups: high-performing provinces (Cluster 0), underserved areas (Cluster 1), and moderately performing regions (Cluster 2). Advanced telecommunication strategies, such as Intelligent Reflecting Surfaces (IRS), UAV-assisted connectivity, and cognitive Device-to-Device (D2D) communication, were incorporated into tailored yearly strategies for each cluster. The findings highlight that IRS deployment, coupled with satellite and UAV solutions, can significantly enhance connectivity in underserved areas. These strategies aim to bridge Indonesia’s digital divide, ensure equitable access to reliable communication services, and foster sustainable development in rural areas